SYNTHESIS AND CHARACTERIZATION OF A TETRAHEDRAL AND MONOMERIC MONOBUTYLTIN COMPOUND WITH Α-HYDROXYISOBUTYRIC ACID - Roberto Santos Barbiéri; Vilma Reis Terra; Allan Kardec Carlos Dias; Walclée de Carvalho Melo (Journal of the Chilean Chemical Society, 2019)
The monobutyltin compound [BuSnLCl2], L = Me2C(OH)COO--, was prepared and characterized by elemental analysis of carbon, hydrogen, chlorine and tin, and infrared, 119mSn-Mössbauer and 119mSn-NMR spectroscopies. In the compound, a tetrahedral tin species, L is coordinated monodentatedly by the oxygen of the deprotonated hydroxyl of the carboxylic group. The compound was studied by the application of TG and DSC in dynamic atmosphere of helium. The termal decomposition mechanism for the compound and TG curve suggests the formation of tin in accordance with their stoichiometry. The Mössbauer parameters of complexes are in agreement with a monomeric structure for the complex in the solid state.